PEMBERDAYAAN MASYARAKAT PETANI PADI SAWAH MELALUI PENGEMBANGAN AGRIBISNIS (Studi Kasus Gapoktan Pebaloran, Kecamatan Curio, Kabupaten Enrekang) - Zulfiana Fitri; Abdul Gafaruddin; Hidrawati Hidrawati (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This research is motivated by the problems that are often faced by farmers from the capital aspect because of the difficulty of getting capital assistance, crop failure, marketing of agricultural products, very low sales of agricultural products due to the lack of human resource ability to manage and maximize their potential. This research aims to find out the form of empowerment of rice paddy farming communities through agribusiness development in Gapoktan Pebaloran District Curio Enrekang Regency. The number of informants in the study was 22. Determination of informants in this study using purposive technique. Data analysis uses qualitative descriptive analysis. The results showed that the form of community empowerment of rice paddy farmers consists of: capital assistance, with capital assistance provided by the government of Rp.100,000,000, - through PUAP. Furthermore, infrastructure development assistance in the form of irrigation and agricultural business roads. Then institutional development, and strengthening business partnerships. Based on the results of this study it is recommended that for farmers that the independence of a farmer should be owned in the management of rice paddy farming business, for the government to pay more attention and further strengthen policies in strengthening the form of empowerment programs.